Prevalence and prognostic value of ventricular conduction delay in heart failure with preserved ejection fraction - Anouk Achten; Jerremy Weerts; Johan van Koll; Mohammed Ghossein; Sanne G.J. Mourmans; Arantxa Barandiarán Aizpurua; Antonius M.W. van Stipdonk; Kevin Vernooy; Frits W. Prinzen; Hans-Peter Brunner-La Rocca; Christian Knackstedt; Vanessa P.M. van Empel (International Journal of Cardiology: Heart & Vasculature)
Background: The pathophysiology of heart failure (HF) with preserved ejection fraction (HFpEF) is heterogeneous and incompletely understood. This study evaluated the presence of a ventricular conduction delay (VCD) phenotype in HFpEF through QRS duration and vectorcardiographic QRS area, and their relation to adverse outcomes. Methods: This study included consecutive ambulatory HFpEF patients. Baseline QRS duration was obtained from an electrocardiogram (ECG). QRS area was derived from vectorcardiographic analyses of the ECG. QRS duration and area were assessed and analysed as categorical (<100 ms, 100–119 ms, ≥120 ms; ≤ 43.1 µVs, >43.1 µVs) and continuous variables to determine the relation to the composite outcome of HF hospitalisation and all-cause mortality. Results: 349 HFpEF patients were included of whom 70 % had a QRS duration < 100 ms compared to 21 % with QRS duration 100–119 ms and 9 % with QRS duration ≥120 ms. 87 (25 %) patients had QRS area >43.1 µVs. Only 4 % had a QRS area ≥69µVs, indicating delayed lateral wall activation. After a median of 3 years follow-up, 30 % of the patients had an adverse outcome. Longer QRS duration but not larger QRS area was associated with more adverse outcomes on both categorical and continuous scales (HR per 5 ms increase = 1.06, P = 0.033). This prognostic association was mainly present in males. Conclusion: HFpEF patients have a low prevalence of a VCD phenotype(9 % QRS duration ≥120 ms;4 % a QRS area ≥69 µVs). However, QRS duration >100 ms was present in 30 % and was an independent predictor for adverse outcomes. Future efforts are needed to understand the mechanisms underlying the association of QRS duration and adverse outcomes, and to determine its clinical implications.